2016
DOI: 10.1111/jse.12184
|View full text |Cite
|
Sign up to set email alerts
|

Embracing the pteridophyte classification of Ren‐Chang Ching using a generic phylogeny of Chinese ferns and lycophytes

Abstract: The phylogenetic relationships of pteridophytes occurring in China were reconstructed using DNA sequences of the three plastid genes, atpA, atpB, and rbcL. The sampling comprised all genera of Chinese pteridophytes-including ferns and lycophytes-with the exception of four small genera. The effort to sample all recorded families and genera in a phylogenetic framework enabled the phylogenetic relationships of all Chinese pteridophytes to be addressed for the first time in a single phylogenetic hypothesis. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 122 publications
2
16
0
Order By: Relevance
“…In addition, infrageneric classification of Pyrrosia was always closely linked to the recognition of the segregate genera Drymoglossum and Saxiglossum 5 , 8 , 29 – 32 . Drymoglossum and Saxiglossum are currently accepted as members of Pyrrosia , which has been confirmed by phylogenetic work 33 35 .…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, infrageneric classification of Pyrrosia was always closely linked to the recognition of the segregate genera Drymoglossum and Saxiglossum 5 , 8 , 29 – 32 . Drymoglossum and Saxiglossum are currently accepted as members of Pyrrosia , which has been confirmed by phylogenetic work 33 35 .…”
Section: Introductionmentioning
confidence: 67%
“…Several molecular phylogenetic studies involved Pyrrosia , some of which revealed that Pyrrosia was monophyletic and Platycerium was a sister group 33 , 36 45 . In the most recently study, Vasques et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although this relationship conflicts with the current understanding of tracheophyte relationships (e.g., Pryer et al, ), Ruhfel et al () showed recently that it was an artifact resulting from high guanine‐cytosine (GC) content. Among ferns, the backbone relationships of the early‐diverging lineages are still not fully resolved, even with much denser sampling (Liu, ). For example, the position of Equisetaceae in this study was consistent to some extent with previous studies that used similar genes (Pryer et al, ; Liu, ), but recent studies based on whole plastid genomes recovered this family as sister to a clade comprising Ophioglossaceae and Psilotaceae (e.g., Gao et al, ; Lu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research on fern phylogeny has mostly relied on plastid genes [ 10 , 12 , 13 ], some combined with a few nuclear genes [ 4 , 5 , 14 ] or morphological traits [ 5 , 11 ]. Due to incomplete lineage sorting (ILS), genes from different resources often show conflicting evolutionary patterns, especially when based on a limited number of samples, and some deep relationships in fern phylogeny remain controversial (Fig.…”
Section: Introductionmentioning
confidence: 99%